KEDUDUKAN NEGARA SEBAGAI PENGELOLA WARISAN ATAS HARTA PENINGGALAN TAK TERURUS MENURUT SISTEM WARIS BURGERLIJK WETBOEK - Oemar Moechthar (Universitas Airlangga, 2017)
The legal system of inheritance in Indonesia is divided into three systems, namely western heirs legal system derived from burgerlijk wetboek (hereinafter referred to as